Accuracy of predicted ear canal speech levels using the VIOLA input/output-based fitting strategy. - Cox RM; Flamme GA; Cox, R M; Flamme, G A (Ear & Hearing (01960202), 1998)
Objective: The Visual Input/Output Locator Algorithm (VIOLA) is a software-assisted method for prescribing amplification targets and selecting a hearing aid to match the targets. Although the procedure calls for selection and fitting of hearing aids in terms of their pure-tone input/output functions in a coupler, it is assumed that a hearing aid that matches the coupler prescription targets will produce specific amplified speech levels in the patient's ear canal. This investigation evaluated the validity of that assumption.Design: Six hearing aids were evaluated. They were representative of linear and compression processing as well as single- and 2-channel designs. The "subject" was a KEMAR manikin with realistic assumed hearing loss and loudness perception characteristics. Each hearing aid was configured to match the subject's VIOLA prescription as closely as possible. Predicted ear canal speech levels were determined using the prescription rules and modified by the differences between coupler prescription targets and coupler performance of the actual hearing aids. With the subject wearing each hearing aid coupled to an unvented earmold, continuous speech was presented in the sound field and measured, after amplification, in the ear canal. The match between observed and predicted levels of amplified speech indicated the validity of the VIOLA assumptions under examination.Results: The match between predicted and observed levels was good for soft speech input levels. As speech input levels increased, the differences between observed and predicted levels also increased, with the largest differences seen for loud speech inputs. When differences were seen between observed and predicted levels, they were always in the direction of lower than predicted ear canal levels. The differences between observed and predicted levels were attributed to the effects of limiting, effects of compression ratio in wide range compression, the individual subject's field-to-microphone transfer function, and the subject's individual real-ear-to-coupler level difference.Conclusions: Ear canal speech levels were reasonably close to predicted values, and the deviations from predicted levels were plausibly accounted for by consideration of hearing aid performance. Thus, the approach used by the VIOLA procedure holds considerable promise for extending clinical control over the complex and interactive parameters of nonlinear hearing aids. The results of this study indicate that selection and fitting of hearing aids using the current VIOLA procedure usually will result in the generation of lower than predicted ear canal speech levels, especially for loud speech inputs. However, the accuracy of the procedure could be improved substantially by modification of the software to account for the effects of limiting and those of the compression ratio in systems with compression thresholds lower than the level of unamplified loud speech.